2016
DOI: 10.1016/j.carbpol.2016.04.094
|View full text |Cite
|
Sign up to set email alerts
|

Producing ultrapure wood cellulose nanofibrils and evaluating the cytotoxicity using human skin cells

Abstract:  Cellulose nanofibril dispersion (50 µg/ml) did not affect the cytotoxicity or metabolic activity of Normal Human Dermal Fibroblasts and Human Epidermal Keratinocytes  Aerogels made of cellulose nanofibrils induced a reduction of metabolic activity by the fibroblasts and keratinocytes, but no significant cell death  Cytokine profiling measuring 27 cytokines revealed that the keratinocytes and fibroblasts did not induce cytokines upon direct exposure to the CNF materials. Due to the nano dimension of the CN… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
128
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 103 publications
(135 citation statements)
references
References 51 publications
6
128
1
Order By: Relevance
“…Nevertheless, it provides information that may be used for comparison purposes, namely with samples under similar conditions. Although the CNF was not tested for LPS contamination, previous studies by Nordli et al (2016) showed that the TEMPO-mediated oxidation performed in alkaline conditions strongly reduces the LPS content in the sample, becoming easier to wash out from the fibres after the oxidation process. Because washing was performed exhaustively in this CNF production it is unlikely that LPS still persists in the sample.…”
Section: Nanocellulose Production and Characterizationmentioning
confidence: 99%
See 1 more Smart Citation
“…Nevertheless, it provides information that may be used for comparison purposes, namely with samples under similar conditions. Although the CNF was not tested for LPS contamination, previous studies by Nordli et al (2016) showed that the TEMPO-mediated oxidation performed in alkaline conditions strongly reduces the LPS content in the sample, becoming easier to wash out from the fibres after the oxidation process. Because washing was performed exhaustively in this CNF production it is unlikely that LPS still persists in the sample.…”
Section: Nanocellulose Production and Characterizationmentioning
confidence: 99%
“…These nanocellulose types are generally considered as nontoxic, although nanocrystalline cellulose could induce low cytotoxicity and immunotoxicity in vitro and in vivo (Clift et al 2011;Yanamala et al 2014). Regarding CNF, the few published studies mainly indicate no relevant cytotoxic, genotoxic or immunotoxic effects (Alexandrescu et al 2013;;Nordli et al 2016;Pitkanen et al 2014;Vartiainen et al 2011). Nevertheless, a recent study by Catalán et al (2017) showed that C57Bl/6 mice exposure by pharyngeal aspiration to CNF produced through TEMPO oxidation led to an acute lung inflammatory response and induced DNA damage in lung cells.…”
Section: Introductionmentioning
confidence: 99%
“…The possibility to create NFC‐based dressings for wound healing applications has been introduced and examined in a series of studies by ourselves and others, with promising results. However, to date, no work has addressed neither the hemocompatibility aspect of NFC‐based materials, nor the possibility of modifying these materials to obtain dressings that aid the first phase of wound healing—hemostasis.…”
Section: Introductionmentioning
confidence: 99%
“…All samples of CNF-based RH sensors showed an expected response to RH changes, that is, decrease of impedance with increase of RH. 16,56 The response of the biocomposite sample with PEG, that is, FS_T3.8_P40, was fast and stable at each level in the tested range. Based on this, we focused our efforts on the comparison between the samples without and with PEG where the sensor characteristic behavior differences were obvious.…”
Section: Sensory Characteristics Of Cnf Filmsmentioning
confidence: 99%
“…The pulp fibers were washed three times with 0.1 M NaOH and autoclaved as described by Nordli et al 56 2,2,6,6-Tetramethylpiperidinyl-1-oxyl (TEMPO)-mediated oxidation (3.8 and 6.0 mmol hypochlorite) was applied as pretreatment. An ULTRA-TURRAX was used for homogenizing the pulp fibers at a concentration of 2 wt %.…”
Section: Cnf Manufacturingmentioning
confidence: 99%